Religiosity of Violence through Pesantren (A Method to Prevent Carok in Madura Tribe of Indonesia) - ., Haris (2017)
The term[1] of carok among Madurese means “fight with honor”. Madurese dialect described it with ‘ecacca erok-orok’ meaning “to slaughter and to mutilate”. Ancient Javanese (Kawi) defined carok as fighting. Celurit was actually symbolizing the weapon used by blater (chivalrous people). Dutch demolished this symbol by condemning Pak Sakera, the originator of someone who lived with celurit, as a rebel despite his status of santri and pious Moslem. However, celurit was then used by Madurese as a weapon in their struggle against Dutch colonizer. Problems of adultery, inherited land, and others conflicts, were often resolved through carok. Reason behind this was to recover self-dignity and self-esteem. Heroism and spirituality within carok was enforced through a phrase ‘etembang pote matah lebbi bagus pote tolang’ (rather than white eye [blind], better is white bone). It means “better die on the ground than bear a shame”. After hundreds years of occupation, Dutch colonizer left Madura Island but carok and celurit were preserved as the admissible way to eliminate adversaries. This culture still existed in Bangkalan, Sampang and Pamekasan. People thought that it was the legacy of their ancestors, but in reality, it was a product of cultural engineering by the Dutch.Carok was men’s way. They came from a family with authority, courage, muscle art skill, and power (either invulnerability or immunity). They may also emanate from the genealogy of hermits. Keywords: carok, religiousity, violence [1] Carok was identified with ‘celurit’ and emerging amidst Madurese since Dutch colonialism in 18th century. Carok symbolized “a chivalrous way” to defend self-dignity (self-esteem). Celurit was the only weapon used in carok. In the days of Pangeran Cakraningrat, Joko Tole and Panembahan Semolo of Madura, people had not been or were not familiar with carok and celurit. The culture of honorary fight was killing adversary in chivalrous way using sword or keris. Celurit was new weapon used by a Madurese legend of Pak Sakera. He was a foreman of sugarcane plantation in Pasuruan. He never left his celurit during his journey to work, his work of monitoring sugarcane workers and farmers, and even his worship at prayer house